SISTEM INFORMASI AKUNTANSI PENGELOLAAN ADMINISTRASI PEMBAYARAN KEUANGAN SEKOLAH BERBASIS CLIENT SERVER - Hani Krisnawati; Praditya Dewi Arumsari (LPPM Universitas Sains dan Teknologi Komputer, 2022)
Technological developments at this time are very advanced in various ways, inviting everyone to find new discoveries, therefore an information processing work system that is fast, precise and accurate is expected to improve service to consumers to achieve goals. MA Miftahul Ulum Ngemplak administration includes payment of Education Development Contribution (SPP), extracurricular money (including: scouts, computers, volleyball and drum bands) and Intra-School Student Organization (OSIS) money up to the preparation of financial reports every day, every month to every years to be reported to interested parties, such as the school treasurer, principal and head of the foundation, and all these payments are still recorded manually. This system has a weakness, namely in terms of recording school administration payments it is less effective because it has to record in triplicate, namely on student payment cards, daily data payment report books, and monthly data payment report books, as well as the process of finding data and submitting student payment reports is not fast. With the existence of a system, it is hoped that later the design can assist in the transaction process for paying tuition fees, UTS, UAS and all expenses at MA Miftahul Ulum Ngemplak, besides being able to produce software applications that aim to increase productivity and support facilities in administrative activities, especially tuition payments. , UTS, UAS and expenditure transactions at MA Miftahul Ulum Ngemplak and the recording process becomes more effective because recording is only once during the school financial administration payment process and speeds up the process of searching for data and submitting school financial administration payment reports